Does the Occurrence of a High-Impact Temporary Incident Disrupt the SERVQUAL Model? Evidence from the Indian Hospitality Industry - Sultana, Mafruza; Barma, Asit K.; Agnes, Ruma (ASEAN Journal on Hospitality and Tourism, 2025)
The occurrence of COVID-19 made the authors seek to find out if the SERVQUAL model holds good during high-impact temporary incidents or if adding new dimensions can improve the satisfaction prediction. The motive of this research is to observe how the five dimensions of the SERVQUAL Model play out during an unusual high-impact temporary event like the COVID-19 pandemic to measure customer satisfaction, and if the COVID protocol measures adopted by the hospitality industry have any impact on the relative importance of the SERVQUAL dimensions on the overall satisfaction of the customers. This study conducted an online survey to gather relevant information. The researchers identified a select group of respondents using the non-probability sampling technique. This work used the Partial Least Squares (PLS) modeling technique to measure customer satisfaction. Adoption of COVID protocols significantly impacts customer satisfaction. Even when the hotel strictly follows the COVID protocols, the empathy and responsiveness shown by the hotel staff and the assurance guaranteed by the hotel about the safety and well-being of the customers have significantly contributed to improving customer satisfaction. The authors found that SERVQUAL as a model stood firm even during a high-impact temporary incident with a negligible increase in R2 value when the hotel industry adopted a new dimension specific to COVID-19 precautions.